Alien fish eradication from high mountain lakes by multiple removal methods: Estimating residual abundance and eradication probability in open populations. Issue 5 (14th March 2021) - Tiberti, Rocco; Buchaca, Teresa; Boiano, Daniel; Knapp, Roland A.; Pou Rovira, Quim; Tavecchia, Giacomo; Ventura, Marc; Tenan, Simone
Abstract: Invasive alien species are among the most important threats to biodiversity. Plans for their eradication have been implemented worldwide but estimating residual population size and eradication probability to assess removal success is complicated by the imperfect detection of residual individuals. Most methods to assess residual abundance and eradication probability rely on the often unrealistic assumption that a population is closed to mortality and recruitment processes during the implementation of removal actions. We extended existing removal models and developed a novel analytical approach to estimate residual population size and derive eradication probability in open populations while accounting for multiple removal methods. We apply this approach to 20 eradication projects in Europe and the United States that used mechanical methods to return high mountain lakes to their original fishless condition. The new removal model incorporates (a) a mechanistic description of the ecological process underlying survival and recruitment probabilities during the eradication period and (b) the use of multiple, concomitant removal methods (i.e. electrofishing, gillnetting, fyke‐netting) at multiple sites simultaneously. We used a subset of 'control' lakes where eradication success was confirmed by more than 5 years of post‐removal surveys to validate the model. For these lakes, eradication success, evaluated by whether the 95% Bayesian credible interval for estimated residual population size encompassed values of <2 individuals, was confirmed in 13 out of 15 lake‐by‐species case studies. In addition, the model correctly assigned an eradication probabilities equal to 0 for the eradications that are still in progress. Synthesis and applications . Our study provides insights into the dynamics of fish populations subject to eradication in high mountain lakes of different countries. In addition, the analytical approach proposed accounts for demographic processes and multiple removal methods in multiple sites and seasons. It can represent an informative tool to estimate residual population size and eradication probability of alien species to optimize eradication efforts and efficacy of conservation actions. The extension to open populations makes the approach useful to evaluate long‐term eradication plans. Abstract : Our study provides insights into the dynamics of fish populations subject to eradication in high mountain lakes of different countries. In addition, the analytical approach proposed accounts for demographic processes and multiple removal methods in multiple sites and seasons. It can represent an informative tool to estimate residual population size and eradication probability of alien species to optimize eradication efforts and efficacy of conservation actions. The extension to open populations makes the approach useful to evaluate long‐term eradication plans. Resumen: Las especies exóticas invasoras suponen una grave amenaza para la biodiversidad de muchos ecosistemas. Varios planes para su erradicación se han implementado en todo el mundo, pero estimar el éxito de la erradicación se complica debido a la imposibilidad de detectar con certeza la presencia de todos los individuos que aún están presentes en el sitio. Los métodos para estimar el tamaño de la población remanente y la probabilidad de erradicación se basan típicamente en la hipótesis, a menudo poco realista, de que no haya mortalidad ni reclutamiento durante el proceso de erradicación, es decir, se tratan como poblaciones cerradas. Por lo tanto, hemos ampliado los modelos de removal existentes y desarrollado un nuevo tipo de análisis para estimar el tamaño de la población remanente y obtener una probabilidad de erradicación para poblaciones abiertas, considerando también la posibilidad de incluir datos de diferentes métodos de captura. Este nuevo modelo se ha aplicado a los datos recogidos durante las acciones de erradicación llevadas a cabo mediante métodos mecánicos de peces introducidos en 20 lagos de alta montaña de Europa y de los Estados Unidos con el fin de restaurar su condición original sin peces. El nuevo modelo incluye i) una descripción mecanicista de los procesos ecológicos que determinan la probabilidad de supervivencia y reclutamiento durante el período de erradicación y ii) la posibilidad de utilizar datos recogidos con el uso simultáneo de diferentes métodos de captura (es decir, pesca eléctrica, pesca con redes agalladeras y trampas de tipo nasa) en diferentes lagos. Para validar el modelo, hemos utilizado, como control, la información de los lagos donde el éxito de la erradicación se había confirmado por más de 5 años de monitoreo. Para estos lagos, el éxito de la erradicación, evaluado en función de si el intervalo de credibilidad estimados al 95% para el tamaño de población remanente incluía valores de menos de 2 individuos, se confirmó en 13 de los 15 casos de estudio. Además, el modelo asignó correctamente una probabilidad de erradicación igual a 0 para las erradicaciones que aún están en curso. Síntesis y aplicaciones . Nuestro estudio proporciona una nueva herramienta que permite planificar y monitorear las acciones de erradicación de peces en lagos de alta montaña en diferentes países. Además, el nuevo enfoque analítico tiene en cuenta los procesos demográficos naturales y el uso de múltiples métodos de captura en diferentes lagos. Este estudio puede proporcionar una nueva herramienta para estimar el tamaño de las poblaciones residuales de especies exóticas y optimizar los esfuerzos de erradicación y la eficacia de las acciones de conservación. La extensión a poblaciones abiertas hace que esta herramienta sea útil para evaluar planes de erradicación a largo plazo. Riassunto: Le invasioni biologiche sono una grave minaccia per la biodiversità. In tutto il mondo sono state condotte molte campagne di eradicazione, ma ottenere una stima della popolazione residua e della probabilità di successo dell'eradicazione può essere complicato a causa dell'impossibilità di rilevare con certezza la presenza di tutti gli individui ancora presenti nel sito. Molti metodi per stimare la numerosità delle popolazioni residue e la probabilità di eradicazione sono basati sull'assunto poco realistico che mortalità e nascite siano nulle durante il processo di eradicazione, i.e., popolazioni chiuse. Perciò, abbiamo esteso i modelli di removal esistenti e sviluppato un nuovo tipo di analisi per stimare la dimensione della popolazione residua e derivare una probabilità di eradicazione per le popolazioni aperte, anche considerando la possibilità di includere dati provenienti da diversi metodi di cattura. Questo nuovo modello è stato applicato ai dati di eradicazione raccolti presso 20 laghi di alta montagna europei e statunitensi trattati con metodi meccanici di eradicazione di pesci introdotti, al fine di ripristinare il loro stato originale privo di pesci. Il nuovo modello include i) una descrizione meccanicistica dei processi ecologici che determinano la probabilità di sopravvivenza e ingresso di nuovi individui durante il processo di eradicazione e ii) la possibilità di usare dati provenienti dall'utilizzo simultaneo di diversi metodi di cattura (i.e., elettropesca, pesca con reti e pesca con nasse) in diversi laghi. Per validare il modello, abbiamo utilizzato un gruppo di casi studio di controllo, dove il successo dell'eradicazione è confermato da più di 5 anni di monitoraggi. Il successo dell'aradicazione è stato confermato in 13 su 15 casi di controllo, quando gli intervalli di credibilità al 95% della popolazione residua stimata includono valori minori di 2 individui. In più, il modello ha assegnato una probabilità di eradicazione pari a 0 per tutti i laghi dove il processo di eradicazione era ancora in corso. Sintesi e applicazioni . Il nostro studio fornisce un nuovo strumento per interpretare la dinamica delle popolazioni ittiche soggette a azioni di eradicazione nei laghi di alta montagna di differenti Paesi. In più, il nuovo approccio analitico tiene in considerazione i naturali processi demografici e l'utilizzo di metodi di cattura multipli in diversi laghi. Questo studio può fornire un nuovo strumento per stimare la dimensione delle popolazioni residue di specie alloctone e per ottimizzare gli sforzi di eradicazione e la loro afficacia conservazionistica. L'estensione alle popolazioni aperte rende questo strumento utile per valutare le azioni di eradicazione di lunga durata. Resum: Les espècies exòtiques invasores suposen una greu amenaça per a la biodiversitat. Els plans per a la seva erradicació s'han implementat a tot el món, però estimar la mida de la població residual i la probabilitat d'èxit de l'erradicació es complica a causa de la impossibilitat de detectar amb certesa la presència de tots els individus que encara són presents en el lloc. La majoria dels mètodes per estimar la mida de la població residual i la probabilitat d'erradicació es basen en el supòsit, sovint poc realista, que la mortalitat i el reclutament són zero durant el procés d'erradicació, com si fos una població tancada. El que hem fet és ampliar els models d'erradicació existents i hem desenvolupat un nou tipus d'anàlisi per estimar la mida de la població residual i obtenir una probabilitat d'erradicació per a poblacions obertes, considerant també la possibilitat d'incloure dades de diferents mètodes de captura. Aquest nou model s'ha aplicat a les dades d'erradicació recollides en 20 llacs d'alta muntanya d'Europa i dels Estats Units tractats amb mètodes mecànics d'erradicació per tal de restaurar la seva condició original sense peixos. El nou model inclou i) una descripció mecanicista dels processos ecològics que determinen la probabilitat de supervivència i reclutament durant el període d'erradicació i ii) la possibilitat d'utilitzar dades recollides amb l'ús simultani de diferents mètodes de captura (és a dir, pesca elèctrica, pesca amb xarxes de tipus solta i trampes de tipus barbol) en diferents llacs. Per validar el model, vam utilitzar com a 'control' un subgrup de llacs on l'èxit de l'erradicació s'havia confirmat després de 5 anys de monitorització posteriors a l'erradicació. Per a aquests llacs, l'èxit de l'erradicació, avaluat en funció de si l'interval creïble bayesià del 95% per a la mida de la població residual estimada, incloïa valors de menys de 2 individus, es va confirmar en 13 dels 15 casos d'estudi. A més, el model va assignar correctament una probabilitat d'erradicació igual a 0 per les erradicacions que encara estan en curs. Síntesi i aplicacions . El nostre estudi proporciona una nova eina per interpretar la dinàmica de les poblacions de peixos subjectes a accions d'erradicació en llacs d'alta muntanya de diferents països. A més, el nou enfocament analític té en compte els processos demogràfics naturals i l'ús de múltiples mètodes de captura en diferents llacs. Aquest estudi pot proporcionar una nova eina per estimar la mida de les poblacions residuals d'espècies exòtiques i optimitzar els esforços d'erradicació i l'eficàcia de les accions de conservació. L'extensió a poblacions obertes fa que aquesta eina sigui útil per a avaluar plans d'erradicació a llarg termini.